2020
DOI: 10.1177/0092055x20952826
|View full text |Cite
|
Sign up to set email alerts
|

Educational Travel for First-Generation Students

Abstract: Research on educational travel has shown significant student outcomes for personal, academic, and professional growth. However, there are financial and cultural barriers that make it harder for some groups of students to participate in programs such as study abroad and shorter-term educational travel. This article examines the unique challenges and opportunities for first-generation and low-income students in these programs. It analyzes a short-term (10-day) educational travel group of exclusively first-genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Community-based research experiences at the undergraduate level are becoming increasingly popular (Kozimer-King and Price 2018). They have been found to provide meaningful and longer-lasting impacts on students in terms of applying key sociological concepts, developing research skills, reflecting on lived experiences, and improving self-efficacy (Dean and Kelly 2020; Greenberg, London, and McKay 2020; Love and Macallory 2021; Mayer et al 2019). However, such experiences should be mindful of the ethical challenges that may be unique to rural people and places.…”
Section: Ideas For Serving and Engaging Rural Fgcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Community-based research experiences at the undergraduate level are becoming increasingly popular (Kozimer-King and Price 2018). They have been found to provide meaningful and longer-lasting impacts on students in terms of applying key sociological concepts, developing research skills, reflecting on lived experiences, and improving self-efficacy (Dean and Kelly 2020; Greenberg, London, and McKay 2020; Love and Macallory 2021; Mayer et al 2019). However, such experiences should be mindful of the ethical challenges that may be unique to rural people and places.…”
Section: Ideas For Serving and Engaging Rural Fgcsmentioning
confidence: 99%
“…At times these faculty serve as advisors, role models, social workers, and even economic developers (Finnegan 2019). Departments should be intentional about engaging FGCS in high-impact activities and removing barriers to participation (Dean and Kelly 2020; Ives and Castillo-Montoya 2020). For example, providing a stipend for students to participate in a summer research opportunity or referring students to national opportunities, such as the McNair Scholars program (https://mcnairscholars.com), would allow students who need to work the ability to gain research experience while also earning money and making valuable connections.…”
Section: Ideas For Serving and Engaging Rural Fgcsmentioning
confidence: 99%
“…Sixty-three percent of students were White, 22 percent were Black, and 7 percent were Latinx in 2021 (Data USA, n.d.). Many of our students are first generation and/or low-income, so the cost of programs is a deciding factor for many (Dallinger 2017; Dean and Kelly 2020; Madhavan and Dlamini 2021). Furthermore, because Louisiana does not have any national parks, most of the participating students had little knowledge of public lands in the United States.…”
Section: But Before We Go To Zion: Definitions Assignments and Assess...mentioning
confidence: 99%
“…Importantly, to increase environmental consciousness as an integral part of global citizenship as well as more egalitarian education, travel study should not be the exclusive domain of the privileged. Short-term study abroad and domestic travel study that involve service learning and/or meetings with community members, for example, can help close the gap and provide students with the same professional and personal benefits as more traditional study abroad (Dallinger 2017; Dean and Kelly 2020; Madhaven and Dlamini 2021; Nordmeyer, Teig, and Bedera 2016).…”
Section: Travel Study Environmental Education and National Parksmentioning
confidence: 99%
“…A considerable volume of research has been dedicated to examining the journeys and obstacles encountered by first-generation college students (FGCS) in their pursuit of higher education. This body of work consistently highlights the distinctive academic and social challenges FGCS face, including unfamiliarity with college norms, constrained financial resources, and limited support networks, all of which can adversely affect their college experience and perceptions of success [ [18] , [19] , [20] ]. For instance, one line of inquiry has revealed that these students frequently navigate unique academic and social barriers, which can impede their progression and sense of belonging within the college environment.…”
Section: Introductionmentioning
confidence: 99%